2014
DOI: 10.1161/circgenetics.113.000305
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants in CCNB1 Associated With Differential Gene Transcription and Risk of Coronary In-Stent Restenosis

Abstract: Background-The development of diagnostic tools to assess restenosis risk after stent deployment may enable the intervention to be tailored to the individual patient, for example, by targeting the use of drug-eluting stent to highrisk patients, with the goal of improving safety and reducing costs. The CCNB1 gene (encoding cyclin B1) positively regulates cell proliferation, a key component of in-stent restenosis. Therefore, we hypothesized that single-nucleotide polymorphisms in CCNB1 may serve as useful tools i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…The recruitment of SMCs to neointimal lesions after PCI in humans is partly under genetic control [ 3 , 5 , 6 ]. Similarly, neointimal hyperplasia after different forms of vascular injury or flow-cessation in mice has been found to be highly strain dependent although little is known about the causative gene variants [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The recruitment of SMCs to neointimal lesions after PCI in humans is partly under genetic control [ 3 , 5 , 6 ]. Similarly, neointimal hyperplasia after different forms of vascular injury or flow-cessation in mice has been found to be highly strain dependent although little is known about the causative gene variants [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The opposite contribution was observed for rs350104CT+CC genotypes. The genotypes associated with poorer cognitive performance in the cohorts of women with BC, rs164390–GT+TT, rs350099–CT+CC, and rs350104–TT, are all hypothesized to lead to lower levels of CCNB1 expression via reduced recruitment of transcription factors to the promotor region of the gene 62. This result is contradictory to anticipated findings, as higher cyclin B levels in breast tissue are associated with more severe cancer phenotypes 63,64.…”
Section: Discussionmentioning
confidence: 86%
“…32,33 Recent research has also revealed that the expression of CCNB1 increased in human thoracic aortic dissection and the genetic variants in CCNB1 correlated with the risk of coronary in-stent restenosis. 34,35 However, the role of CCNB1 in cardiac remodeling is still unknown. In this article, we observed that CCNB1 was the most significantly up-regulated gene in both cell division and cell cycle pathways, which were among the most affected pathway associated with up-regulated genes in KO TAC mice.…”
Section: Discussionmentioning
confidence: 99%